Liquid-Liquid Equilibrium of Poly(Ethylene Glycol) 6000 + Sodium Succinate + Water System at Different Temperatures - Selvaraj Raja; Vytla Ramachandra Murty (The Scientific World Journal)
Phase diagrams and the compositions of coexisting phases of poly(ethylene glycol) (PEG) 6000 + sodium succinate + water system have been determined experimentally at 298.15, 308.15, and 318.15 K. The effects of temperature on the binodal curve and tie lines have been studied. The binodal curves were successfully fitted to a nonlinear equation relating the concentrations of PEG 6000 and sodium succinate, and the coefficients were estimated for the formentioned systems (low AARD, high R2, and low SD). Tie-line compositions were estimated and correlated using Othmer-Tobias and Bancroft equations, and the parameters were reported. The effect of temperature on the phase-forming ability has been studied by fitting the binodal data to a Setschenow-type equation for each temperature. The effective excluded volume (EEV) values were also calculated from the binodal data, and it was found out that the values increased with an increase in the temperature. Furthermore, the effect of MW of PEG on the phase diagram has been studied and verified.